Pelatihan dan Pendampingan Peningkatan Keterampilan Akuntansi Pada UMKM "Sala Lauak Kito" - Lisa Amelia Herman; Josephine Sudiman; Dedy Djefris (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The existence of Micro, Small and Medium Enterprises (MSMEs) in Indonesia is quite dominating and is the backbone that supports economic growth and provides jobs. Its existence needs to be appreciated and developed by providing access to financing, guidance and assistance so that it can develop its business. Training and mentoring activities are carried out in order to improve accounting skills for one of the micro businesses in Padang City "UD. Sala Lauak Kito. There is a need for partners to gain knowledge and understanding of accounting books and the ability to make financial reports. Until now, partners have not carried out the bookkeeping process so that cost and income information is not generated accurately. Implementation of activities consists of three stages: planning, implementation and final stage. Overall, all stages were carried out for 2 months. From planning to final stage. The training was carried out for 1 day and mentoring was carried out 1 month after the training. The method of implementation is in the form of material explanation presentations, exercises, discussions, question and answer discussions and independent learning through modules. The training material provided is in the form of knowledge related to the accounting cycle from recording to financial reporting. After the implementation of the activities there is an increase in accounting knowledge, the creation of complete and valid financial information, the existence of documented bookkeeping, the preparation of financial reports as information from the business. The output of this activity is the publication of print/digital newspapers and activity videos via YouTube media.